25-Hydroxyvitamin D Levels and the Risk of Dementia and Alzheimer's Disease: A Dose–Response Meta-Analysis - Chen, Hanze; Xue, Weishuang; Li, Jinwei; Fu, Kailei; Shi, Han; Zhang, Beidi; Teng, Weiyu; Tian, Li (Frontiers in Aging Neuroscience, 2018)
Background and Purpose: Conclusions of previous cohort studies on the relationship between 25-hydroxyvitamin D level and the risk of dementia and Alzheimer’s disease were not consistent. Thus, we performed a dose–response meta-analysis to evaluate this relationship by summarizing cohort studies. Methods: Pubmed, Embase, Cochrane and Web of Science databases were searched for relevant studies. Cohort studies concerning the association between 25-hydroxyvitamin D level and dementia or Alzheimer’s disease were included. Results of studies were pooled and the dose–response relationship was determined using a random-effect model. Results: Ten cohort studies, with 28,640 participants were included. A significant inverse relationship was found between 25-hydroxyvitamin D level and the risk of dementia and Alzheimer’s disease. In addition, we found a linear dose–response relationship in that a 10 nmol/L increase in 25-hydroxyvitamin D level may lead to a 5% decrease in the risk of dementia (relative risk, 0.95; 95% confidence interval, 0.93–0.98) and 7% in the risk of Alzheimer’s disease (relative risk, 0.93; 95% confidence interval, 0.89–0.97). Conclusion: Plasma or serum 25-hydroxyvitamin D concentration was inversely related to the risk of dementia and Alzheimer’s disease, consistent with a linear dose–response relationship.